The diagnostic value of ultrasound examination in temporal arteritis - DADONIENĖ, Jolanta; JATUŽIS, Dalius; LAURINAVIČIUS, Arvydas (Acta medica Lituanica, 2010)
Introduction. Temporal arteritis (TA) is usually diagnosed according to clinical criteria, and temporal artery biopsy is considered as a golden standard for the diagnosis. Temporal artery biopsy is a surgical intervention on a head site and is not well-tolerated by the patients. As an alternative for temporal artery investigation, ultrasound examination may be used. The aim of this pilot study was to evaluate the performance of ultrasound examination of a temporal artery of patients with and without TA, but with similar clinical findings.Materials and results. Thirteen patients seen at Vilnius University Hospital Santariškių Klinikos during 2006–2009 with suspicion of TA were included into this study, and ultrasound examination of their both right and left superficial temporal arteries was performed. Eight patients were diagnosed with TA according to clinical criteria, and 5 patients had headaches of another origin. Two patients had a biopsy-proven diagnosis. The thickened wall (“halo” sign) and / or stenosis / occlusion were found on ultrasound examination in three patients. The presence of abnormality was found in five patients from the setting of TA patients, and no abnormalities were detected in the control group. Although the groups were very small and the data scanty, we consider the sensitivity of the abnormalities detected by ultrasound to be 62.5%, and the specificity was close to 100% in this pilot study.Conclusions. Authors recommend bilateral ultrasound examination of temporal arteries for patients with suspicion of giant cell arteritis (temporal arteritis). Our pilot study showed a sufficient sensitivity of this diagnostic test, although it greatly depends on the experience and skills of the performer.Keywords: temporal arteritis, ultrasound examination